Pressure‐Induced Perovskite‐to‐non‐Perovskite Phase Transition in CsPbBr3. Issue 2 (27th January 2021) - Noculak, Agnieszka; Boehme, Simon C.; Aebli, Marcel; Shynkarenko, Yevhen; McCall, Kyle M.; Kovalenko, Maksym V.
Abstract: The expanding range of optoelectronic applications of lead‐halide perovskites requires their production in diverse forms (single crystals, thin‐ and thick‐films or even nanocrystals), motivating the development of diverse materials processing and deposition routes that are specifically suited for these structurally soft, low‐melting semiconductors. Pressure‐assisted deposition of compact pellets or thick‐films are gaining popularity, necessitating studies on the pressure effects on the atomic structure and properties of the resulting material. Herein we report the phase transformation in bulk polycrystalline cesium lead bromide from its three‐dimensional perovskite phase (γ‐CsPbBr3 ) into the one‐dimensional polymorph (δ‐CsPbBr3 ) upon application of hydrostatic pressure (0.35 GPa). δ‐CsPbBr3 is characterized by a wide bandgap of 2.9 eV and broadband yellow luminescence at 585 nm (2.1 eV) originating from self‐trapped excitons. The formation of δ‐CsPbBr3 was confirmed and characterized by Raman spectroscopy, 207 Pb and 133 Cs solid‐state nuclear magnetic resonance, X‐ray diffraction, absorption spectroscopy, and temperature‐dependent and time‐resolved photoluminescence spectroscopy. No such phase transition was observed in colloidal CsPbBr3 nanocrystals. Abstract :